Implikasi Aliran Filsafat Pendidikan Islam Pada Manajemen Pendidikan - Ahmad Salim (Universitas Alma Ata, 2014)
The philosophy of Islamic education has less effect on the development of Islamic education journey. The concept of thinking of educational course not only from logical thinking but also from the revelation. It be the pattern of the development process as a key of instruction. There are many Islamic educational philosophy course but writer only discuss the conservative, religious-instrumental rational and pragmatic philosophy in this paper. While the figures to be discussed is Al-Ghazali represents the first course, the Ikhwan al-Safa represent the second course while Ibn Khaldun represent the third course. The effect of the course of philosophical education on management education is implementing educational philosophy in many management functions, namely the planning, implementation (classroom management)and evaluation.